PENINGKATAN PENGETAHUAN TENTANG PERILAKU HIDUP BERSIH SEHAT (PHBS) KEPADA WARGA DESA TANJUNGPURA KABUPATEN KARAWANG - Lilis Suryani (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2023)
The Clean and Healthy Living Behavior (CHLB) is a government health promotion program aimed at enhancing community self-reliance in maintaining and improving health. CHLB at the household level strives to empower members to be conscious, willing, and capable of adopting clean and healthy living behaviors to preserve and enhance their health. This initiative not only prevents the risk of diseases but also shields individuals from health threats while actively participating in the broader public health movement. The Clean and Healthy Living pattern should commence at the household level, recognizing that a healthy household serves as a developmental asset for the future that requires safeguarding. Given the susceptibility of certain household members to both infectious and non-infectious diseases, it becomes imperative for households to adhere to Clean and Healthy Living Behaviors (CHLB) to mitigate these risks effectively. This study underscores the importance of integrating CHLB into daily household routines to foster a healthier community and contribute to long-term societal development.